Enhancing Learner Autonomy through Collaborative Learning in a Distance Language Classroom of Morphology Class - Yasa Ayatina Ashidiq (ENLIT, 2022)
Learner autonomy concept appears crucially in amid of pandemic which makes student and teacher do a distance classroom. Students should aware of their learning capability in order to avoid learning loss.Therefore, this research aim to seek how well students apply learner autonomy concept in collaborative learning. Data were taken from morphology class evaluation among 42 English Literature students of UIN Sunan Gunung Djati Bandung which was collected from the google form record which later will be a document. The activities of teaching and learning was held from 6th September 2021 to 25th December 2021 in a distance learning via google meet. There were 42 students involved. The researcher applied document analysis technique in analyzing the student responses toward the learning activity. There were some characteristics that students applied in their learner autonomy and collaborative learning such as independence, confidence, responsibility, creativity and awareness. There were 17 data independence, 1 datum classified as confidence aspect, 15 data about responsibility, 3 data of creativity characteristic, 2 data regarding motivation and 4 data related with awareness. The student in this Morphology class had succeeded in applying the concept of learner autonomy through collaborative learning. They were able to collaborate with peers in group work even though in a distance learning. The success of their learning could be seen from the existence of the autonomy aspects.